Molecular dynamics-guided reaction discovery reveals endoperoxide-to-alkoxy radical isomerization as key branching point in α-pinene ozonolysis - Huan Yang; Umberto Raucci; Siddharth Iyer; Galib Hasan; Thomas Golin Almeida; Shawon Barua; Anni Savolainen; Juha Kangasluoma; Matti Rissanen; Hanna Vehkamäki; Theo Kurtén (Nature Communications)
Abstract Secondary organic aerosols (SOAs) significantly impact Earth’s climate and human health. Although the oxidation of volatile organic compounds (VOCs) has been recognized as the major contributor to the atmospheric SOA budget, the mechanisms by which this process produces SOA-forming highly oxygenated organic molecules (HOMs) remain unclear. A major challenge is navigating the complex chemical landscape of these transformations, which traditional hypothesis-driven methods fail to thoroughly investigate. Here, we explore the oxidation of α-pinene, a critical atmospheric biogenic VOC, using a novel reaction discovery approach based on molecular dynamics and state-of-the-art enhanced sampling techniques. Our approach successfully identifies all established reaction pathways of α-pinene ozonolysis, as well as discovers multiple novel species and pathways without relying on a priori chemical knowledge. In particular, we unveil a key branching point that leads to the rapid formation of alkoxy radicals, whose high and diverse reactivity help to explain hitherto unexplained oxidation pathways suggested by mass spectral peaks observed in α-pinene ozonolysis experiments. This branching point is likely prevalent across a variety of atmospheric VOCs and could be crucial in establishing the missing link to SOA-forming HOMs.